Pricing Models Using Real Data - Obremski, Tom (Teaching statistics, 2008)
Summary A practical hands‐on classroom exercise is described and illustrated using the price of an item as dependent variable throughout. The exercise is well‐tested and affords the instructor a variety of approaches and levels.